Peranan Faktor Cuaca terhadap Infeksi dan Perkembangan Penyakit Bercak Ungu pada Bawang Merah - Bambang Hadisutrisno; Sudarmadi Sudarmadi; Siti Subandiyah; Achmadi Priyatmojo (Jurnal Perlindungan Tanaman Indonesia, 1995)
Purple blotch disease caused by Alternaria porri (Ell.) Cif. is one of the most important diseases on shallots. The farmers have been using fungicides as a reliable control method, however, the chemical control method has to be considered for the negative effect on the environment and the danger to the other species and causes the resistance to a certain pesticide. Therefore, it is important to develop other method that is safe, effective, and efficient, like the use of climatic data to decide the control strategy. The result of the study on ecology of purple blotch disease carried out at the experimental station in Kramat-Tegal, Kledung-Temanggung, and KP4 Kalitirto in dry and rainy season (1991/1992) suggested that climatic factors played on important role on the daily conidium dissemination of Alternaria porri and on the intensity of purple blotch disease. Daily conidium dissemination which was one of the important component in the epidemy of purple blotch disease was influenced by the temperature, relative humidity, and the wind velocity. Conidium dissemination was occurred both during the day and night and at 10.00 am-14.00 pm when the air temperature and wind velocity were high with low relative humidity, conidium dissemination was maximum. On the other hand, at 22.00 pm – 02.00 am there was minimum conidium dissemination. The result on the effects of leaf wetness period on disease intensity suggested that high humidity was not the only factor caused disease infection but it has to be supported by the presence of thin film water on the leaf surface at least for 4 hours since the attachment of the conidia on the leaves.